ASSESSING JAPANESE FEMALE COLLEGE STUDENT FEELINGS ABOUT MATHEMATICS LEARNING AREA CONTENTS - Nishikawa, Tomoko (PEOPLE: International Journal of Social Sciences, 2020)
This study was designed to examine Japanese female college students’ feelings toward mathematics that they had learned before beginning college study. The 235 surveyed participants were all Japanese college students from the humanities course of a two-year junior college in a local city in Japan. For this investigation, respondents were divided into groups based on their feelings about mathematics. They were scrutinized using conjoint analysis for their learning anxieties about specific learning contents. The analysis consisted of assessing these students’ awareness of ‘being good at’, ‘neutral’, and ‘being not good at’ one specific aspect of mathematics relative to others. These groups were characterized. Results revealed differences in the perceptions of difficulty specific to the learning areas. These findings suggest the importance of providing female students with appropriate learning content from elementary school to high school, depending on their feelings about mathematics. These findings might help teachers plan mathematics learning classes for secondary education.